Pengaruh Good Corporate Governance dan Karakteristik Perusahaan Terhadap Nilai Perusahaan dan Profitabilitas Sebagai Variabel Intervening: Studi Empiris pada Perusahaan Makanan dan Minuman yang Terdaftar di BEI Tahun 2019-2021 - Dikadijayati; Triyono (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to evaluate the impact of Good Corporate Governance and Company Characteristics on Firm Value, with Profitability as an intervening variable. The study employs a quantitative method utilizing secondary data from annual reports of companies registered on the Indonesia Stock Exchange during the 2019-2021 period. The data collection technique used is a literature review (documentation). The total data analyzed in this research amounts to 75, derived from 25 samples multiplied by the three years of the study (2019-2021). The data analysis methods applied include descriptive statistics and classical assumption tests, which consist of autocorrelation, heteroscedasticity, multicollinearity, and normality tests. Additionally, this study employs the Sobel test, path analysis, and hypothesis testing. The results of this study indicate that managerial ownership, independent commissioners, company size, and leverage do not affect firm value. Profitability has been proven to have a significant impact on firm value. Managerial ownership and independent commissioners do not contribute to profitability. Conversely, company size and leverage have a significant impact on profitability. Profitability cannot mediate the relationship between managerial ownership, independent commissioners, company size, and leverage on firm value.